Andinia wayqechensis (Orchidaceae), a new species from southern Peru - Martel, Carlos; Collantes, Benjamín; Maire, Anne-Laure; Thoerle, Lisa (Phytotaxa, 2016)
Andinia wayqechensis, from the Peruvian cloud forest, is proposed as a new species. The species is similar to Andinia pentamytera, but differs in the leaves with a tridentate apex (vs. a denticulate apex); and flowers with oblong, shortly acuminate sepals with irregularly lacerate margins (vs. narrowly ovate-triangular, long-acuminate sepals with entire margins); petals with irregularly lacerate margins and short-acuminate apices (vs. with entire margins and long-acuminate apices); and a labellum with the erect lateral lobes curving above and largely concealing the column (vs. below the exposed column). A description, illustrations, information about its habitat and distribution, and a key to the species of Andinia are provided.